Effects of renewal pruning on soil moisture and growth of apple tree - LI Ming-xia; DU She-ni; BAI Gang-shuan; GENG Gui-jun (浙江大学学报. 农业与生命科学版, 2012)
Compared with long-branch pruning of apple tree in Weibei Plateau of Shaanxi Province, the effects of renewal pruning on soil moisture in 0-500 cm soil depths and the growth of apple tree at final full productive stage were determined. The results showed that soil moisture in 0-240 cm depths was significantly increased by renewal pruning, and soil moisture below 240 cm soil layer had not significant difference between renewal pruning and long-branch one from sprout stage to defoliation stage. The peak of soil evapotranspiration intensity by renewal pruning was higher and delayed 30 d than that by longbranch one, but the average intensity had not significant difference between renewal pruning and longbranch one during the growth period of apple tree. Renewal pruning reduced significantly the total number of branches per tree in next year, the proportion of short and foliage branches, and increased significantly the proportion of long, medium branches. Meanwhile, renewal pruning increased significantly fruit yields and fruit mass, improved significantly orchard economic value and water output ratio, but had not significant difference in water consumption compared with long-branch pruning. As a result, renewal pruning improve soil moisture and promote growth of apple tree, which is an appropriate pruning method for apple tree at final full productive stage in Weibei Plateau of Shaanxi Province.